PENGARUH KESADARAN ATAS PELAYANAN, KEPRCAYAAN DIRI DAN NORMA SUBJECTIVE TERHADAP NIAT PENGGUNAAN DIGITAL BANKING : THE EFFECT OF SERVICE AWARENESS, SELF-CONFIDENCE AND SUBJECTIVE NORMS ON INTENTION TO USE DIGITAL BANKING - Azmii Lathifah; Gita Rahayu; Belinda Mora Siagian (TECHNOBIZ : International Journal of Business, 2025)
This study aims to examine the influence of service awareness, self-efficacy, and subjective norms on the intention to use digital banking services in Indonesia. The results indicate that all three independent variables have a positive and significant effect on the intention to use digital banking. Service awareness was found to be a significantly positive initial cognitive factor that enhances intention to use digital banking. Self-efficacy also showed a significant positive effect that suggesting that individuals who feel capable of operating digital banking applications are more likely to engage in digital transactions. Likewise, subjective norms were found to have a positive influence on behavior, confirming the role of social pressure and peer support in shaping users’ adoption behavior. These findings reinforce the TPB, TAM, and UTAUT frameworks, suggesting that cognitive, psychological, and social factors interact synergistically to explain the adoption of digital banking. Practically, the results recommend that banks enhance user awareness through targeted education, design onboarding features that strengthen self-efficacy, and leverage social and community-based strategies to encourage the intention to use digital banking services in Indonesia.